PENGARUH EARNING PER SHARE, RETURN ON EQUITY, PRICE EARNING RATIO, DAN RETURN ON ASSET TERHADAP HARGA SAHAM (Studi Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia) - Gitaya, Nindya; Djazuli, Atim (Jurnal Ilmiah Mahasiswa FEB, 2014)
This research aims to determine the effect of Eaning Per Share, Return On Equity, Price Earning Ratio, and Return On Assets to theÂ  stock price of the manufacturing company in Indonesia Stock Exchange. The type of this research is explanatory research. This research use 13 companies as the sample that acquired by purposive sampling method. The analysis method in this resesarch are multiple linier regression and classical assumption, while the hypothesis test is using F test and t test. The result showed that Eaning Per Share, Price Earning Ratio, and Return On Asset have a significant effect on Stock Price, while Return On Equity have no significant effect on Stock Price. It means that the change of Eaning Per Share, Price Earning Ratio, and Return On Asset will affect the stock price change. Based on the result Earning Per Share, Price Earning Ratio, and Return On Asset can be used by investor as a consideration in making investment decisions. Keywords: Eaning Per Sharre, Return On Equity, PriceEearning Ratio, and Return On Assets, Stock price.